KARAKTERISTIK MEKANIK DAN BALISTIK KOMPOSIT Al-8Zn-4Mg-20 VOL.% SiC HASIL PROSES SQUEEZE CASTING DAN PERLAKUAN PENUAAN - Sabarati, Absaralita; Adhipura, Panji; Sofyan, Bondan T. (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Armoured Personnel Carrier (APC) as a means to support the mobility of TNI must have high toughness so that they are not easily penetrated by bullets. The APCs are commonly made of steel due to their excellent toughness and ballistic properties, however, it has a high density that reduces their mobility. Therefore, an alternative material is needed, which is lighter but remains tough. One option is Metal Matric Composites (MMC). This research studied a composite with Al-8Zn-4Mg alloy as the matrix and 20 vol. % SiC as the reinforcement. The composite was melted in a muffle furnace, stirred at 500 rpm, and squeeze-cast at the pressure of 20 tons. The samples were then solution-treated at 500°C for 1 h and aged at 200°C for up to 100 h. Characterization included hardness and impact testing, optical microscopy, and Scanning Electron Microscope - Energy Dispersive X-ray (SEM-EDX). The samples were then thermal coated by the High-Velocity Oxygen Fuel (HVOF) method using WC-Co particles. The coated samples underwent ballistic testing in accordance with NIJ 0108.01 standard by using a type III 7.56 mm caliber projectile. The results show that the hardness and impact energy increased with aging due to the formation of Mg2Si and Mg3Zn3Al2 precipitates. Peak hardness conditions after aging for 2 h generated hardness of 90,25 HRB and impact energy of 3 Joules. The composite plate failed and was penetrated by a type III 7.56 mm caliber projectile.